Чому залізобетонні, а не металеві силоси? - Жук, Олег; Муха, Володимир Миколайович; Куянов, Володимир Вікторович; Миропольський, Олександр Михайлович (My University, 2021)
У статті наведено інформацію щодо залізобетонних конструкцій для аграріїв, які пропонує компанія ТОВ «Вольф Систем». Описані основні переваги залізобетонних конструкцій та їхні особливості. The article provides information on reinforced concrete structures for farmers, offered by Wolf System company. The main advantages of reinforced concrete structures and their features are described.
Keywords: залізобетонні конструкції; залізобетонні резервуари; залізобетонні силоси; reinforced concrete structures; reinforced concrete tanks; reinforced concrete silos